Determining quality traits of some concentrate feedstuffs and assessments on relations between the feeds and the traits using biplot analysis - Basbag, Mehmet; Sayar, Mehmet Salih; Cacan, Erdal; Karan, Halil (Parlar Scientific Publications, 2021)
The study was conducted to determine quality traits of some concentrate feedstuffs. For this purpose, commonly used eight concentrate feedstuffs samples were subjected to laboratory analyzes with three replications. According to the analysis results the means of investigated traits were ranged as follow; dry matter contents (DM) 87.29-92.13%, crude ash contents (CAC) 1.57-7.21%, organic matter contents (OM) 81.35-89.01%, crude protein contents (CP) 7.07-45.94%, crude oil contents (CO) 0.89-9.07%, crude cellulose contents (CS) 3.40¬ 39.50%, metabolic energy values (ME) 3112.1¬ 3265.3 kcal/kg, nitrogen-free extract (NFE) 28.50¬ 72.95%, calcium contents (CA) 0.20-1.48%, magnesium contents (MG) 0.02-0.37%, phosphor contents (P) 0.27-0.50%, potassium contents (K) 0.36¬ 2.60%, acid detergent fiber (ADF) contents 9.12 - 44.03%, neutral detergent fiber (NDF) contents 11.12-62.88%, digestible dry matter (DDM) contents 54.60-80.24%, dry matter intake (DMI) 1.91¬ 13.16% and relative feed value (RFV) values 80.77-809.68. Additionally, biplot analysis revealed that there were positive relationship among ADF, NDF, CS, CO and DM traits. Accordingly; safflower meal (1) and cottonseed meal (2) went ahead for these traits. Similarly, positive relationship was determined among ME, RFV, DDM, DMI, NFE and K traits. Exclusively, the ground corn grain (3) was found superior for the important traits, so it was found as having best quality feedstuff. © 2021 Parlar Scientific Publications. All rights reserved.
Keywords: ADF; Biplot analysis; Concentrate feedstuffs; Crude protein; Macro minerals; NDF